A Truth Table of Skocpol’s Argument - Foran, John Foran (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The Teaching Comparative-Historical Methods in Sociology compilation of syllabi is intended for two audiences: those who already teach comparative and historical methods at the university level, and those who wish to introduce it into their repertoire. Only syllabi which bear centrally on the methods of teaching comparative and historical sociology, rather than, as in past editions of this teaching set, courses which substantively address comparative and historical issues in sociology, such as globalization and development, the welfare state, revolutions and social movements, or topics to do with culture, the family, deviance, race/ethnicity, or gender were included.